Effort distribution and tactical behaviour on the men`s 1500 metres at the World Athletics Indoor Championships Belgrade 2022 - Casal García, N.; López Del Amo, J. L. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The 1500 meters is a middle-distance discipline. Due the distance of the race, tactic behaviour is important to achieve a good performance. Placing yourself in the first positions at the start of the race can be overrated since the medallists are usually decided in the last laps due the final "kick"(Sandford, Day & Rogers, 2019) or also to the lower loss of speed in the last 200 meters (Hanley, Stellingwerff & Hettinga, 2019). The aim of this study is to analyse the distribution of effort and tactical behaviour during the high-level mens 1500-meter race.